Exploration of Lamiaceae in Cardio Vascular Diseases and Functional Foods: Medicine as Food and Food as Medicine - Chakrabartty, Ishani; Mohanta, Yugal Kishore; Nongbet, Amilia; Mohanta, Tapan Kumar; Mahanta, Saurov; Das, Nibedita; Saravanan, Muthupandian; Sharma, Nanaocha (Frontiers in Pharmacology, 2022)
In the current scenario, cardiovascular disease (CVD) is one of the most life-threatening diseases that has caused high mortality worldwide. A number of scientists, researchers, and doctors are now resorting to medicinal plants and their metabolites for the treatment of different diseases, including CVD. The present review focuses on one such family of medicinal plants, called Lamiaceae, which has relieving and preventive action on CVD. Lamiaceae has a cosmopolitan distribution and has great importance in the traditional system of medicine. The different members of Lamiaceae exhibit a wide range of activities like antioxidant, antihyperlipidemic, vasorelaxant, and thrombolytic effect, both in vitro and in vivo – these are mechanisms that contribute to different aspects of CVD including stroke, heart attack, and others. The plants harbor an array of bioactive compounds like phenolic acids, flavonoids, alkaloids, and other phytochemicals that are responsible for these actions. The review also highlights that these plants are a rich source of important nutrients and minerals like omega-3 and hence, can serve as important sources of functional foods – this can have an additional role in the prevention of CVDs. However, limitations still exist, and extensive research needs to be conducted on the Lamiaceae family in the quest of developing new and effective plant-based drugs as well as functional foods that can be used in the treatment and prevention of cardiovascular diseases worldwide.